2022
DOI: 10.1111/joop.12413
|View full text |Cite
|
Sign up to set email alerts
|

Why do leaders engage in destructive behaviours? The role of leaders’ working environment and stress

Abstract: Complementing previous research on antecedents of destructive leadership, we examined the role of work stressors in the emergence of active and passive destructive leadership behaviours. Building on conservation of resources theory, we examined direct and indirect relations between leaders' perceptions of workload, role ambiguity and intragroup conflict on ratings of their own destructive leadership, as well as mediating paths through perceived stress. We used a two-wave survey design consisting of a random sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 74 publications
1
4
0
4
Order By: Relevance
“…These findings are in line with those of De Clercq et al (2021). To elaborate more, when nurses are asked to engage in compulsory citizenship involuntarily, it results in OCB, while in the long run, it results in work–family conflict (Dongrey and Rokade, 2023; Tafvelin et al , 2023). Besides, when individuals encounter work–family conflict as a result of extra roles, it manifests as weariness and exhaustion (Ekowati et al , 2023).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These findings are in line with those of De Clercq et al (2021). To elaborate more, when nurses are asked to engage in compulsory citizenship involuntarily, it results in OCB, while in the long run, it results in work–family conflict (Dongrey and Rokade, 2023; Tafvelin et al , 2023). Besides, when individuals encounter work–family conflict as a result of extra roles, it manifests as weariness and exhaustion (Ekowati et al , 2023).…”
Section: Discussionsupporting
confidence: 81%
“…Excessive employee engagement at work may be beneficial for organizations in completing tasks and achieving their citizenship goals (Zampetakis and Lanivich, 2023). However, extra work that does not result in compensation can make employees feel that their expectations are inconsistent with reality and lead to conflict (Tafvelin et al, 2023). Therefore, this paper proposes that: H7.…”
Section: Cost Of Organizational Citizenship Behaviorsmentioning
confidence: 99%
“…In other words, the demands placed on managers’ shoulders should not prevent them from fulfilling their managerial duties, which can be broadly categorized into two main categories: task direction and psychological support. Tafvelin et al (2023) reported that a higher workload was significantly associated with more passive/cowardly leadership behaviors. In our study, we found that the components of leadership responsibilities such as task direction and psychological support, as proposed by Katz and Kahn (1978) and Lanaj and Jennings (2020) , contributed to the perceived heaviness of the manager’s workload.…”
Section: Discussionmentioning
confidence: 99%
“…Men det är inte bara de negativa aspekterna som smittar av sig, utan även chefens engagemang verkar spridas till resten av organisationen (Schaufeli & Salanova, 2007). Ledarskapet påverkar således även medarbetarnas välbefinnande och prestation (Tafvelin, Lundmark & Stenling, 2022). Trots att första linjens chefer har en central och komplex roll i organisationer, har forskningen sällan fokuserat på deras organisatoriska och sociala arbetsmiljö (Edvik & Muhonen, 2022).…”
Section: Bakgrundunclassified